Acylated ghrelin protects aorta damage post-MI via activation of eNOS and inhibition of angiotensin-converting enzyme induced activation of NAD(P)H-dependent oxidase. (3rd September 2018) - Eid, Refaat A.; El-Kott, Attalla Farag; Zaki, Mohamed Samir Ahmed; Eldeen, Muhammad Alaa; Al-Hashem, Fahaid H; Alkhateeb, Mahmoud A.; Alassiri, Mohammed; Aldera, Hussain
ABSTRACT: NAD(P)H dependent oxidase derived-reactive oxygen species (ROS) due to activation of the renin-angiotensin-aldosterone system (RAAS) in blood vessels postmyocardial infarction MI or during the HF leads to endothelium dysfunction and enhanced apoptosis. Acylated ghrelin (AG) is a well-reported cardioprotective and antiapoptotic agent for the heart. AG receptors are widely distributed in most of blood vessels, suggesting a role in the regulation of endothelial function and survival. This study investigated if AG can protect aorta of rats' postmyocardial infarction (MI)-induced damage and endothelial dysfunction. Adult male rats were divided into four groups of (1) Sham, (2) Sham + AG, (3) MI, and (4) MI + AG. Vehicle (normal saline) or AG (100 µ/kg) was administered to rats for 21 consecutive days, after which, numerous biochemical markers were detected by blot. Both histological and electron microscope studies were carried on aortic samples from MI-induced rats. AG increased protein levels of both total and phosphorylated forms of endothelial nitric oxide synthase (eNOS and p-eNOS, respectively). Only in MI-treated rats, AG prevented the decreases in the levels of reduced glutathione (GSH) and superoxide dismutase (SOD) and lowered levels of malondialdehyde (MDA) and glutathione disulfide (GSSG). Concomitantly, it lowered the increased protein levels of angiotensin-converting enzyme (ACE), p22phox and cleaved caspase-3 and prevented the aorta histological and ultrustructural abnormalities induced by MI.